Sharia Compliance Analysis of Heavy Equipment Rental Services Based on Ijarah Provisions in Islamic Economics: A Case Study of CV Putra Jaya Mandiri, West Bandung Regency - Ansori , Faisal (Institut Agama Islam Persis Bandung, 2026)
The construction sector in Indonesia has experienced rapid growth, generating substantial demand for heavy equipment rental services. However, empirical research examining whether such rental practices conform to the principles of ijarah the Islamic contract governing the lease of usufruct remains limited, particularly in the context of conventional construction service companies. This study analyses the heavy equipment rental system at CV Putra Jaya Mandiri, a construction equipment rental firm in West Bandung Regency, West Java, against the normative provisions of ijarah in Islamic economics. A qualitative case study design was employed, with primary data obtained through in-depth interviews with the company's President Director, supplemented by participant observation and document analysis. Data were analysed using the Miles–Huberman interactive model, comprising data condensation, display, and conclusion drawing. The findings reveal that the existing rental system at CV Putra Jaya Mandiri operates through eight stages: registration and booking, verification and approval, rental contract, payment, equipment delivery and handover, monitoring and maintenance, equipment return, and transaction closure. Although the system is procedurally functional, it has not fully complied with the principles of ijarah, particularly regarding the explicit avoidance of gharar (uncertainty), the structure of late-return penalties, and the documentation of contract elements. The study contributes to the literature on the operationalisation of muamalah principles in conventional Indonesian SMEs and recommends concrete reforms including transparent pricing, written and detailed ijarah contracts, ta'zir-based rather than riba-based late penalties, and clear documentation of usufruct transfer to align the company's practices with sharia provisions